Criminal Justice Personal Data Protection - Sekulić, Miloš B.; Grujic, Gordan (Glasnik Advokatske komore Vojvodine, 2020)
Abstract: The right to privacy is one of the fundamental human rights that serves to realize a man as a social being and protect the private spheres of his life. Even though that can be looked at in different ways, in today’s conditions of information and communications technologies expansion, it is largely related to personal data and their availability to the third person. In that sense, the right to privacy is also protected via personal data protection. The basis for such a protection in the Serbian law has already been implemented in the Constitution of Serbia, and by adopting a new Personal Data Protection Law, the legislator has shown their determination to intensify and expand that protection. When it deals with criminal justice protection, it is provided under the Criminal Code for the purpose of prescribing a separate criminal offence or unauthorized personal data collection from Article 146 of the Criminal Code. The authors of this scientific paper will try to expose the threat to the right to privacy and personal data, and to give a clearer picture of how criminal justice protection of these values is realized in the Serbian law by presenting the elements of the aforementioned crime.Key words: the right to privacy, the unauthorized personal data collection, Criminal Code, Personal Data Protection Law.
Keywords: Key words: the right to privacy, the unauthorized personal data collection, Criminal Code, Personal Data Protection Law.